DOI: 10.22215/etd/2014-10567
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Sequence Recognition: Is Familiarity or Ordinality the Primary Factor in Performance?

Abstract: Lyons and Beilock (2009) suggested that the degree of ordinal association in 3-digit numerical sequences is a primary factor in the speed and accuracy with which people recognize numerical sequences. Using two experiments I examined an alternative hypothesis, specifically that having automatic access to a larger set of memorized (i.e., familiar) sequences is the determining factor in performance. Participants were shown four types of ordered stimuli, with corresponding unordered sequences. In general, highly-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 65 publications
(75 reference statements)
3
35
0
Order By: Relevance
“…That said, it may be that reversed distance effects are not so much indicative of a fundamental property of number symbols but are more just a by‐product of other numerical processes. For instance, one account of reversed distance effects is that they are essentially a consequence of our familiarity with the count sequence (Bourassa, ; Franklin et al, ; LeFevre & Bisanz, ; Lyons & Beilock, ; Turconi et al, ). However, the current data do not support this view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That said, it may be that reversed distance effects are not so much indicative of a fundamental property of number symbols but are more just a by‐product of other numerical processes. For instance, one account of reversed distance effects is that they are essentially a consequence of our familiarity with the count sequence (Bourassa, ; Franklin et al, ; LeFevre & Bisanz, ; Lyons & Beilock, ; Turconi et al, ). However, the current data do not support this view.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the current leading explanation for the reversed distance effect is that it is a by‐product of familiarity with a recited sequence (e.g., the counting or alphabetical sequence: Bourassa, ; Franklin et al, ; LeFevre & Bisanz, ; Lovelace & Snodgrass, ; Lyons & Beilock, ; Turconi et al, ). That is, one directly retrieves and matches an ordered sequence with a subset of the count list: for instance, 1‐2‐3 and 5‐6‐7 are more familiar and thus more rapidly identified as “in‐order” than 1‐3‐5 or 4‐6‐8.…”
mentioning
confidence: 99%
“…Lyons and Beilock argued that the order judgment task could be very useful for understanding how numerical knowledge was represented, more generally, citing the correlation with working memory ability as potentially linking ordinal processing skill with mathematical proficiency. Bourassa (2014) conducted two experiments exploring the role of familiarity rather than ordinality in sequence judgments. Four types of three single-digit stimuli were used (counting, balanced, arithmetic, neutral) with two conditions (ascending, descending).…”
Section: Ordered Sequencesmentioning
confidence: 99%
“…Accordingly, Bourassa concluded that rather than ordinality, the familiarity of a number sequence was the chief factor in recognizing the sequence. Lyons and Beilock (2011) used the same order judgment task as Lyons and Beilock (2009) and Bourassa (2014) to examine the relationship between non-symbolic number discrimination ability and arithmetic skill. They concluded that number ordering ability fully mediated the relationship between approximate number system ability and mental arithmetic ability.…”
Section: Ordered Sequencesmentioning
confidence: 99%
See 1 more Smart Citation